Hubungan Hutang Riba dengan Kesehatan Mental: Analisis Berita sebagai Objek Penelitian - Mutia Rahmah; Meilenda Astuti; Dina Marni (Kampus Akademik Publiser, 2025)
This research aims to explore the relationship between debt transactions involving usury (riba) and their impact on individuals' mental health. The method used in this study is qualitative, with a discourse analysis approach to news articles discussing the topic of usury and its effects on individuals, both in economic and psychological contexts. Through this analysis, we examine how the media portrays the connection between usury and mental health disorders, as well as the psychological impact of debt transactions involving usury. The findings of the study indicate that news reports tend to highlight the negative effects of usury-based debt on mental health, including stress, anxiety, and depression. This research provides insights into the role of the media in shaping public perception of this issue. It shows that there is a significant relationship between usury-based debt and mental health, as reflected in the news. The media plays an important role in shaping public perception and can be used as a tool to raise awareness of this issue.